THE EFFECT OF JOB SATISFACTION OF THE EMPLOYEES OF INSURANCE COMPANIES WITH REGIONAL DIRECTORATES IN ANKARA ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Third Sector Social Economic Review, 2020)
The success of the employees in the organization and the individual work performance they exhibit are undoubtedly directly related to the sense of satisfaction and commitment of the work on the individual. Individuals who are satisfied with their job are those who aim to provide more value to the organization, are spiritually committed to the organization and ready to exhibit organizational citizenship behavior. Within the scope of the research, it was tried to determine the effect of job satisfaction of organizational citizenship behavior of sub-dimensions of insurance company employees who have regional directorate in Ankara. The results of the research findings were supported by similar studies in the literature. As a result of the data obtained, it has been observed that individuals who have reached the job satisfaction dimension in insurance companies also exhibit OCB. This study also provides insights for managers in the insurance sector to increase the level of job satisfaction of their employees or to select more willing individuals to pursue insurance activities in the recruitment process.
Keywords: Job Satisfaction; Organizational Citizenship Behavior; Insurance Sector